Materials Science Resources on the Web. - Lorraine J. Pellack (Issues in Science and Technology Librarianship)
This guide to materials sciences resources includes reference tools and educational resources related to materials that are freely available on the Internet and do not require subscription or registration on the part of individual researchers to access them. Most of these resources were created by educational institutions, scientific organizations, or are personal projects of materials scientists.